Democracy and leadership : on pragmatism and virtue - Weber, Eric Thomas (Lexington Books, 2013)
In Democracy and Leadership, Eric Thomas Weber draws from Plato's virtues of the ideal city, updated with democratic values and insights from John Dewey, to present both a general and a democratic theory of leadership. Central to the project is the democratic turn away from thinking of leadership as persons to thinking of it as a process open to all.